Measurement of draw-length alterations in the final pull in archery - Fozzy Moritz, E.; Haake, S.; Edelmann-Nusser, J.; Heller, M.; Hofmann, M.; Ganter, N. (The Engineering of Sport 6, Volume 2 Developments for Disciplines, 2006)
In aiming it is important that an archer`s draw-length is quite constant and that the clicker position is only a few millimeters behind the tip of the arrow. At the end of the aiming phase the archer pulls back the arrow a little bit before he releases the shot. This is called the final pull. (1993) measured the alteration of the draw-length indirectly using an electromechanical device that was fixed to the grip and to the lower limb of the bow, but it is very time-consuming and complex to affix this electromechanical device to a bow. The aim of this paper was to describe a system developed to measure the draw-length in the final pull that is easy to handle and to research the final pull in highly skilled archers. The alteration of the draw-length was measured by acquiring the bending of the clicker using a strain gage that is fixed to the clicker: The clicker position during aiming is only a few millimeters behind the tip of the arrowhead. Therefore each alteration of the draw-length leads to an alteration of the bending line of the clicker because of the shape of the arrowhead. Seven archers (two male, five fe-male), all participants at the Junior World Championships and German National Championships performed 66 shots at 30m indoors. Each archer shot with his own personal bow, and the alterations of the draw-length in the final pull were acquired. The results suggest that irregularities in the final pull, especially the so-called shrinking , have a negative influence on the archers` score.